Analisis Rasio Keuangan dan Ukuran Perusahaan Terhadap Kondisi Financial Distress Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2015-2017 - Atina Atina; Elvi Rahmi (Universitas Negeri Padang, 2019)
This study aims to analyze the effect of financial ratios and company size on the financial distress condition of manufacturing companies. Financial distress is measured by an interest coverage ratio, a ratio that is smaller than 1 in the category of financial distress.the financial ratio in this study use liquidity ratios measured by the current ratio, leverage ratio as measured by debt to total asset ratio, and profitability ratio measured by return on investment. The size of the company in this study uses a proxy ln for total assets. The population in this study is manufacturing sector companies in 2015-2017. The sampling technique uses purposive sampling.the sample used inthis study was 69 companies consisting of 24 companies categorized as financial distress and 45 non-financial distres.data analysis techniques using logistic regression analysis with dummy cariables. The results showed hat the liquidity ratio had a significant negative effect, leverage ratio has no significant effect, profitability ratios have a negative and significant effect,and firm size does not significantly influence financial distress. For company manager, it is recommended to pay attention to the factors that influence financial distress in order to be able to overcome the problem earlier. For the next researchers is expected to add a number of other variables that are suspected to have an influence of financial distress and it is recommended to choose other research objects, in order to expand the research objects so that it is able to generalize the result of the study and use other types of financial distress measurement in addition to the interest coverage ratio (ICR). Keyword: liquidity, leverage, profitability, firm size, financial distress